South atlantic: Brazil-Africa relations in the field of security and defense - Aguilar, Sérgio Luiz Cruz [UNESP] (My University, 2013)
South-South Cooperation has become one of the axis of the Brazilian Foreign Policy, especially when related to Africa. Besides the economic, political and technologic areas, among others, the Brazilian government created a series of cooperation agreements with many African countries in the field of security and defense. This paper analyses the objective and reach of the actions concerning South-South Cooperation between the government of Brazil and the African countries, especially the ones from Atlantic Africa, making use of a bibliography related to the subject and sources derived from the Ministry of External Affairs and the Ministry of Defense.
Keywords: Africa; Brazil; Foreign policy; South atlantic; South-south